Pengaruh Pendidikan Kesehatan Reproduksi Dengan Metode Mentoring Terhadap Pengetahuan Kesehatan Reproduksi Pada Remaja SMP N 4 Palembayan 2014 - Mutia Kosasi, Siti; Sinthania, Debby (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
Reproductive health is a state of complete physical, mental, and social whole, not only free from disease or disability in all aspects relating to the reproductive system, functions, and processes. Reproductive health issues has increased every year as sexually transmitted diseases and HIV / AIDS. This research aims to look at the influence of reproductive health education with mentoring methods to adolescent reproductive health knowledge SMP N 4 Palembayan 2014. Type of quantitative research with research design Preeksperimen by design one group pretest-posttest. The population in this research all students / student of class VII and VIII SMP N 4 Palembayan using multistage random sampling technique of sampling. The number of respondents who were sampled as many as 15 people. This research uses data analysis techniques Paired Samples Test. The results of a thorough statistical test p-value = 0.000 (p